Analisa Promosi Penjualan dan Periklanan terhadap Hasil Penjualan Air Mineral - Sumarsid -; Atik Budi Paryanti (JABE (Journal of Applied Business and Economic), 2019)
PT. Tirta Investama (Danone Group) is a company manufacturer of mineral water with the AQUA brand. Because of the many companies that produce similar products i.e. mineral water then the competition happens to be very tight. To be able to compete in the market of mineral water PT. Tirta Investama did a promotional strategy including sales promotions and advertising for all products of mineral water  AQUA.  Based on the results of the analysis of the multiple correlation coefficient obtained correlation coefficient value of X1cost of sales promotions and X2  the cost of advertising is  0.976. Thus the cost of sales promotions and advertising fees have a very strong relationship and positive results against sales of mineral water AQUA packaging 600 milliliters PT. Tirta Investama. Based on the results of the analysis of multiple linear regression can be known that any increase in the cost of sales promotions per USD 1,-, it will result in an  increment amounting to Rp 0,952 sales results. Whereas an increase in the cost of advertising per Rp l-then increment will result in proceeds of $1,279,-thus it can be concluded that if companies do plan to add to the cost of advertising or promotional then the sales volume will increase.Based on the results of the analysis of the determining coefficient (KP) obtained registration = 0.952 or 95.2%. milliliter on means a percentage of the sales promotion costs and influence the cost of advertising against product sales results AQUA mineral water packaging 600 milliliteron PT. Tirta Investama amounted to 95.2% is affected by other factors that are not the meticulous writer. Calculation based on hypothesis test with t-test shows that the variable cost of  sales promotions, as well as variable costs partially influential advertising significantly to sales results. And based on the hypothesis test with test F it can be concluded  that  the cost of sales promotions and advertising costs simultaneously affect significantly  to sales of mineral water AQUA packaging 600 milliliters on PT. Tirta Investama.